Adenosine deaminase enzyme activity is increased and negatively correlates with catalase, superoxide dismutase and glutathione peroxidase in patients with Behçet's disease: original contributions/clinical and laboratory investigations - Kuddusi Erkiliç; Cem Evereklioglu; Mustafa Çekmen; Abdullah Özkiris; Fuat Duygulu; Hakki Dogan (Hindawi Limited, 2003)
Aim: Behçet's disease (BD) is an inflammatory vasculitis with immunologic, endothelial and neutrophil alterations. Adenosine deaminase (AD) is a marker of T-cell activation and is related to the production of reactive oxygen species by neutrophils with the production of NO•, O2•-, H2O2 and OH•. We reported increased tumour necrosis factor-α, soluble interleukin-2 receptor, interleukin-6, interleukin-8 and NO• in active BD. As there is a relation between cytokines, T cells and oxidative stress in inflammatory diseases, this study further evaluated: (1) plasma AD activity and its correlation with acute phase reactants; (2) thiobarbituric acid-reactive substances (TBARS) as an indicator for lipid peroxidation; and (3) antioxidant enzymes superoxide dismutase (SOD), glutathione peroxidase (GSHPx) and catalase in patients with BD. The effect of disease activity and correlations between the measured parameters were explored.